Pendular Voting - Volker Britz; Hans Gersbach (ETH Zurich, CER-ETH - Center of Economic Research, 2021)
We introduce a democratic procedure with voting-based proposals called "Pendular Voting". It works as follows: An agenda-setter chooses a proposal meant to replace a given status quo. In the first stage, a random sample of the population votes on the proposal. The result is made public, which may reveal information about the distribution of preferences in the electorate. Depending on the outcome, a third option (next to the proposal and the status quo) is added: This option is either closer to or more distant from the status quo than the original proposal. Then, in a second stage the entire electorate expresses pairwise social preferences over the status quo, the initial proposal, and the third option. We investigate the manipulability and exploitation of this voting procedure and its welfare effects. We show that manipulation is limited or absent and that exploitation can be avoided. Regardless of whether the agenda-setter is altruistic or selfish, Pendular Voting leads to welfare gains in expectation.
Keywords: C72; D70; D72; 330; Democracy; Manipulation; Information Sharing; Referendum